Serum Vitamin D Level in Chronic Obstructive Pulmonary Disease and its Relation with Severity: A Single Centre Study - Pant, Pankaj; Thapa, Shovit; Das, Santa K; Bam, Niraj (Journal of Institute of Medicine Nepal, 2019)
Introduction: Chronic obstructive pulmonary disease (COPD) is a public health problem of epidemic proportion. Several studies have shown low serum vitamin D levels in patients with COPD. The aim of this study was to compare serum vitamin D level in patients with Global Initiative for Chronic Obstructive Lung Diseases (GOLD) COPD stage II, III and IV with controls and correlate serum vitamin D level with severity of COPD. Methods: A cross sectional study was conducted from June 2014 to November 2015 at Tribhuvan University Teaching Hospital (TUTH). A total of 154 subjects were enrolled for study that consisted of 77 cases of COPD and 77 controls for comparison. Participants were taken from medical wards and outpatient department. COPD staging was done as per GOLD guidelines and stage II, III and IV were labeled as advanced COPD cases. Both descriptive and inferential statistics were performed in SPSS version 20. Results: Stage II, III and IV COPD were 30%, 36% and 34% respectively. Mean serum vitamin D level was 15.16±7.19 ng/ml in COPD cases and 33.99±12.37 ng/ml in healthy controls showing statistically significant relation of low serum vitamin D in patients with advanced COPD (p <0.0001). Serum vitamin D was found to be in decreasing trend with increasing severity of COPD. Conclusion: Patients with advanced COPD (GOLD stage II, III and IV) had low serum vitamin D levels compared to normal population and serum vitamin D level correlated with GOLD severity in Nepalese patients with COPD.